BUILD STUNNING REAL-TIME VFX WITH UNREAL ENGINE 5 start your journey into unreal particle systems to create realistic visual effects using Niagara - Andurlekar, Hrishikesh (Packt Publishing Ltd., 2023)
Create professional real-time particle systems and particle asset creation workflows for games with the power of Niagara and Unreal Engine 5 Key Features Explore how Niagara can make your games pop by creating stunning particle systems in Unreal Engine 5 Level up your VFX skills and enhance your employability in a competitive market Build various particle system projects to reinforce your learning and put your new knowledge into practice Book Description While no game would be complete without visual effects, the ever-evolving VFX industry churns out stellar digital environments that can make your games stand out from the crowd. Build Stunning Real-time VFX with Unreal Engine 5 is here to help you boost your creativity using Niagara to make jaw-dropping particle systems backed by the power of Unreal Engine 5--without a line of code. This handy guide for VFX artists takes you through the principles and concepts of designing particle systems and design workflows, along with the architecture of Niagara, Unreal Engine 5's VFX system. Throughout the book, you'll build a series of mini projects that will put your particle system knowledge to the test. As you advance, you'll cover topics such as creating your own custom modules, debugging workflows, and controlling particles with blueprints, and conclude by working on two projects that will bring everything together into a neat package. By the end of this VFX book, you'll have a deeper understanding of particle systems, improving your skills, portfolio, and the chances of being employed by studios using Unreal Engine 5. What you will learn Brush up your vector mathematics skills Access and create namespaces in Niagara Add a Niagara system to a Blueprint actor Create a particle system with dynamic inputs Publish a custom module for your team members to use Create Niagara Scratch modules Enable your particle emitters to communicate using event handlers Control Niagara systems using Blueprint public variables Who this book is for This book is for visual effects artists transitioning to real-time virtual production workflow as well as beginners looking to learn Niagara for games and other real-time applications. Game programmers, 3D generalists, and game designers interested in adding VFX for their game and metaverse projects will also find this book useful. A basic understanding of Unreal Engine 5, blueprints, as well as layout, materials, and lighting in Unreal Engine is expected.